Sociability of patrol police officers as a key professionally important competence: an empirical study - О. О. Yevdokimova; Y. S. Ponomarenko (Law and Safety)
The psychological analysis of the concept of "sociability" in the field of legal psychology is revealed, which is defined by researchers as a conscious act in communication, aimed at establishing friendly and trusting relationships. The purpose of the article is an empirical study of the psychological structure of the sociability of patrol police officers with different levels of communicative control. The study involved M. Snyder's "Diagnostic Methodology for Assessing Self-Control in Communication", with the help of which we divided the subjects into two groups: with low and high levels of communicative control. The first group consisted of subjects with a low level of communicative control in the number of 14 people, the second group included students with a high level of communicative control in the number of 25 people. 7 respondents with an average level were excluded from further research. O. Krupnov's "Test of judgments of the personality sociability studying" was used to diagnose the main components of sociability. For mathematical and statistical processing, cluster analysis using the k – means method was used. Quantitative processing of the results was carried out using Student's t-test.